Voluntourism: Motivations of Gen Z Participants in Bali - Ni Putu Evi Wijayanti; Ni Komang Anggy Septiani; Putu Ayu Aryasih; Laras Ayu Esty Nariswari (Politeknik Pariwisata Makassar, Indonesia, 2024)
Voluntourism is becoming increasingly popular among Generation Z (Gen Z) in Indonesia. This study examines the motivations of Gen Z volunteer tourists who participate in voluntourism activities in Bali. This study used a qualitative descriptive approach. The informants comprised twenty-six Gen Z tourists in Indonesia, all selected through non-probability and snowball sampling. The result shows that Gen Z tourists are motivated by push and pull factors, including helping others, gaining new experiences, meeting new friends, personal development and growth, cultural interest, visiting Bali, and personal interest in specific volunteering activities. This study provides an in-depth insight into how Gen Z views voluntourism as a means to explore exotic destinations such as Bali and as an opportunity to contribute to the local community positively. The implications of these findings can provide valuable guidance for the tourism industry and volunteer organizations to develop more relevant and meaningful voluntourism programs for Gen Z.